Analysis of Sales Budget Preparation in Preparing Production Cost Budgets (A Study of Home Industry UD Usaha Jaya) - Yanuarmawan, Dion; Dja’far, Veri Hardinansyah (Journal of International Accounting, Taxation and Information Systems, 2025)
This study aims to analyze the preparation of the sales budget used in preparing the production cost budget at UD Usaha Jaya. The data used consist of company data from the previous three years. This study is a type of quantitative research using both primary and secondary data. The Least Square method is used for sales forecasting and separating semi-variable costs. The results indicate that the 2024 sales budget served as the basis for the production cost budget, which includes raw material costs, direct labor, and factory overhead. However, the study found that the preparation of both sales and production cost budgets did not follow standardized procedures, leading to significant discrepancies between planned and actual figures. A key weakness of this study is its limited scope, focusing on a single home industry, which may reduce the generalizability of the findings. Additionally, reliance on historical internal data may not fully capture market dynamics or external factors affecting demand. The study recommends that the company adopt a more structured approach to budgeting and consider integrating digital budgeting tools to improve forecasting accuracy and cost control.